Innate immune receptors in platelets and platelet‐leukocyte interactions - Dib, Paula Ribeiro Braga; Quirino‐Teixeira, Anna Cecíllia; Merij, Laura Botelho; Pinheiro, Mariana Brandi Mendonça; Rozini, Stephane Vicente; Andrade, Fernanda Brandi; Hottz, Eugenio Damaceno (Journal of leukocyte biology, 2020)
Platelets are chief cells in hemostasis. Apart from their hemostatic roles, platelets are major inflammatory effector cells that can influence both innate and adaptive immune responses. Activated platelets have thromboinflammatory functions linking hemostatic and immune responses in several physiological and pathological conditions. Among many ways in which platelets exert these functions, platelet expression of pattern recognition receptors (PRRs), including TLR, Nod‐like receptor, and C‐type lectin receptor families, plays major roles in sensing and responding to pathogen‐associated or damage‐associated molecular patterns (PAMPs and DAMPs, respectively). In this review, an increasing body of evidence is compiled showing the participation of platelet innate immune receptors, including PRRs, in infectious diseases, sterile inflammation, and cancer. How platelet recognition of endogenous DAMPs participates in sterile inflammatory diseases and thrombosis is discussed. In addition, platelet recognition of both PAMPs and DAMPs initiates platelet‐mediated inflammation and vascular thrombosis in infectious diseases, including viral, bacterial, and parasite infections. The study also focuses on the involvement of innate immune receptors in platelet activation during cancer, and their contribution to tumor microenvironment development and metastasis. Finally, how innate immune receptors participate in platelet communication with leukocytes, modulating leukocyte‐mediated inflammation and immune functions, is highlighted. These cell communication processes, including platelet‐induced release of neutrophil extracellular traps, platelet Ag presentation to T‐cells and platelet modulation of monocyte cytokine secretion are discussed in the context of infectious and sterile diseases of major concern in human health, including cardiovascular diseases, dengue, HIV infection, sepsis, and cancer. Graphical Review on how innate immune receptors engagement in platelets modulates the immune response to infectious diseases, sterile inflammation, thrombosis, and cancer.